Size-dependent separation of graphene oxide by deformation of packed-gel in a chromatographic column. Issue 7 (2nd May 2020) - Takaoka, Yuji; Esaki, Shohei; Sakaguchi, Koichi; Fujisawa, Tomotsumi; Unno, Masashi; Morisada, Shintaro; Ohto, Keisuke; Kawakita, Hidetaka
ABSTRACT: A deformable gel-packed chromatographic column was used to separate as-synthesized graphite oxide with different sizes. The synthesized gel (56 µm) was deformed by pressure of the fluid flow and the gaps in the gels showed a range of sizes. A suspension of graphene oxide (0.1 g/L, 10 mL) was injected, and graphene oxide in the elution had a size at 0.56 μm and 0.14 μm, whereas in half upper and bottom domain of the gel layer graphene oxide had a size at 33 µm and 2.9 µm, respectively, demonstrating that graphene oxide suspension was separated by size through gel layer.